Bimodal TBCs with low thermal conductivity deposited by a powder-suspension co-spray process. Issue 8 (August 2018) - Zhang, Wei-Wei; Li, Guang-Rong; Zhang, Qiang; Yang, Guan-Jun; Zhang, Guo-Wang; Mu, Hong-Min
Abstract: Advanced thermal barrier coatings (TBCs) with better thermal barrier performance are required by both advanced gas turbine and air engine. In this work, novel bimodal TBCs with low thermal conductivity were deposited and characterized by a novel co-spray approach with both solid powder and suspension. Experimental and finite element analyses were used to optimize the process parameters to prepare the specific morphology nanostructure features. With a comprehensive understanding on the influence of spraying parameters on the morphology of nano-particles, homogeneous nano-particle heaps with a large aspect ratio were introduced to conventional layered coatings by plasma co-spraying with suspension and solid powder. Co-sprayed bimodal microstructure composite coatings resulted from both wet suspension droplets and molten particle droplets exhibited low thermal conductivity. The thermal conductivity of the composite coating was 1/5 lower than that of the counterpart coatings by conventional plasma spraying with solid powder. This study sheds light to the structural tailoring towards the advanced TBCs with low thermal conductivity.